Systemic Factors Effecting Human Beta-Defensins in Oral Cavity - Atalay, Nur; Balci, Nur; Gürsoy, Mervi; Gürsoy, Ulvi Kahraman (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Human beta-defensins are host defense peptides with broad antimicrobial and inflammatory functions. In the oral cavity, these peptides are produced mainly by the keratinocytes of the epithelium; however, fibroblasts, monocytes, and macrophages also contribute to oral human beta-defensin expressions. The resident and immune cells of the oral cavity come into contact with various microbe-associated molecular patterns continuously and simultaneously. The overall antimicrobial cellular response is highly influenced by local and environmental factors. Recent studies have produced evidence showing that not only systemic chronic diseases but also systemic factors like hyperglycemia, pregnancy, the long-term use of certain vitamins, and aging can modulate oral cellular antimicrobial responses against microbial challenges. Therefore, the aim of this narrative review is to discuss the role of systemic factors on oral human beta-defensin expressions.